EXPERIMENTAL COMPRESSIVE STRENGTH AND MODULUS OF ELASTICITY OF MASONRY - Budiwati, Ida Ayu Made (Jurnal Ilmiah Teknik Sipil, 2009)
Compressive strength and Modulus of elasticity of masonry are significant parameters when considering structural masonry design. This paper presents those masonry properties which were determined experimentally. Three types specimens made of clay brick masonry and concrete block masonry were built. They were tested in compression until failure and conducted in accordance with the BS EN 1052- 1:1999. Properties of structural units and the mortar were also determined. Results show that the mean compressive strength of the mortar, clay brick units and concrete block units are 4.2 N/mm2, 63.0 N/mm2 and 12.8 N/mm2 respectively. The characteristic compressive strength of masonry made of clay brick is 11.2 N/mm2 and that made of concrete block is 7.2 N/mm2. The failure of the masonry tested in compression was due to development of tensile cracks parallel to the axis of the loading. Modulus of elasticity of masonry was close to 1000 fk which is a formula given in Eurocode 6.
Keywords: clay brick, concrete block, mortar, masonry, compressive strength, modulus of elasticity.